Analysis of the Operational Performance of TPS 3R and its Development Potential Towards Indonesia's Zero Waste 2050 Target - Fairuz Alyka; Gabriel Soedarmini Boedi Andari (Journal of Social Research, 2025)
Waste management remains a major challenge in Indonesia, requiring innovative and sustainable solutions to achieve the national goal of Zero Waste by 2050. One strategic approach is the development of Reduce, Reuse, Recycle Waste Processing Sites (TPS 3R), which aim to reduce the volume of waste disposed of in final landfills (TPA). This study analyzes the operational performance of TPS 3R and explores their potential to enhance waste management efficiency. A mixed-methods approach was employed, combining quantitative analysis of TPS 3R operational data with qualitative insights gathered through interviews with TPS 3R managers, government officials, and community members. The findings reveal that TPS 3R operations face key challenges, including limited funding, underdeveloped regulatory frameworks, and low community participation in waste sorting activities. To address these issues, this study proposes strategic recommendations to strengthen TPS 3R effectiveness through policy enhancement, increased financial support, and optimized waste processing technologies. With proper implementation, TPS 3R holds significant potential to serve as a cornerstone in achieving Indonesia's Zero Waste 2050 vision.